Acute Toxicity Studies Of Fixed Dose Combination Of Ceftriaxone+Sulbactam+Ethylenediaminetetraacetic Acid In Swiss Albino Mice And Sprague Dawley Rats - MANU CHAUDHARY; KRISHNARAJU V (International Journal of Pharma and Bio Sciences, 2012)
The acute toxicity study of Ceftriaxone+Sulbactam+Ethylenediaminetetraacetic acid was investigated to offer a solution for the treatment of bacterial infection caused by beta lactam resistant pathogens. A single intra venous injection at the dose levels of 50 mg/Kg, 250 mg/Kg and 500 mg/Kg body weight were administered to Swiss albino mice and Sprague dawely rats (both male and female), where as control groups received normal saline. General behaviour , signs of toxicity, body weight, food and water consumption, and mortality were observed daily for 14 days. At the end of the study , hematological, biochemical, morphological and microscopic parameters were also determined. No toxicological meaningful difference, hazardous symptoms or death were observed in the acute toxicity test which indicates that a single i.v dose of Ceftraixone+sulbactam+EDTA combination at the dose levels of 50 mg/Kg, 250 mg/Kg and 500 mg/Kg body weight was not lethal in both mice and rats (male/female), and suggest a safe use in humans